2008
DOI: 10.2190/pm.38.4.g
|View full text |Cite
|
Sign up to set email alerts
|

Buddhist Values are Associated with Better Diabetes Control in Thai Patients

Abstract: Buddhist values may promote diabetes self-care among Thai patients. Further research is needed to evaluate the relationship of Buddhist values to diabetes-specific health behaviors and neuroendocrine outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
0
13
2
Order By: Relevance
“…The internal consistency of the four instruments in both the pilot and final study was found to be relatively high; the alpha coefficients for DSMQ were 0.73 and 0.94. The alpha coefficient of the pilot study was slightly lower but the final study result was higher than the alpha coefficient found by [9] Schmitt et al. (2013) (0.84) and is still considered acceptable.…”
Section: Methodscontrasting
confidence: 59%
See 2 more Smart Citations
“…The internal consistency of the four instruments in both the pilot and final study was found to be relatively high; the alpha coefficients for DSMQ were 0.73 and 0.94. The alpha coefficient of the pilot study was slightly lower but the final study result was higher than the alpha coefficient found by [9] Schmitt et al. (2013) (0.84) and is still considered acceptable.…”
Section: Methodscontrasting
confidence: 59%
“…Thai DM researchers developed the Buddhism Value Questionnaire (BVQ) in 2008 to examine the associations of Buddhist values with medication and dietary self-care, healthcare use, and HbA1c level among Thai T2DM patients. The original study found that Buddhist values may promote positive self-care behaviors among Thai people with T2DM [9]. The BVQ contains seven items about beliefs in Buddhist teaching and practices and could be rated from 1 (Not at all) to 5 (A great deal) based on their adherence to those practices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] On the other hand, stronger Buddhist values have been associated with better diabetes self-care including diet, medications, and doctor visits and better glycemic control in some populations. [8]…”
Section: Diabetes Among Buddhist Populationsmentioning
confidence: 99%
“…Recent most of studies revealed unsatisfactory internal consistency for the revised scale with Cronbach’s αs lower than .70 (Costa, Pereira, & Pedras, 2012; Janzen Claude, Hadjistavropoulos, & Friesen, 2014; Kroese, Adriaanse, & De Ridder, 2012; Kroese, Adriaanse, Vinkers, van de Schoot, & de Ridder, 2014; Trouilloud & Regnier, 2013; Weinger et al, 2005), limiting the utility of the revised tool. Nevertheless, the revised SDSCA has been translated into cross-cultural versions, such as Chinese, Tai, Korean, Turkish, Arabic, Portuguese, and Maltese (Choi et al, 2011; Cosansu & Erdogan, 2014; Gao et al, 2013; Gatt & Sammut, 2008; Gucciardi, Demelo, Lee, & Grace, 2007; Jarab, Alqudah, Mukattash, Shattat, & Al-Qirim, 2012; Kav et al, 2010; Keeratiyutawong, Hanucharurnkul, Eramo Melkus, Panpakdee, & Vorapongsathorn, 2006; Navicharern, 2012; Nyunt, Howteerakul, Suwannapong, & Rajatanun, 2010; Shi, Ostwald, & Wang, 2010; Sowattanangoon, Kochabhakdi, & Petrie, 2008; Tang, Pang, Chan, Yeung, & Yeung, 2008; Vivienne Wu et al, 2008; Wu, Courtney, et al, 2007; Wu, Huang, et al, 2011; Xu et al, 2008). But, most cross-cultural versions did not achieve acceptable internal consistency, especially for diet subscale (Choi et al, 2011; Cosansu & Erdogan, 2014; Gatt & Sammut, 2008; Gucciardi et al, 2007; Kav et al, 2010; Tang et al, 2008; Xu et al, 2008).…”
Section: Resultsmentioning
confidence: 99%